Effects of Hydrogen on the Phase Relations in Fe‐FeS at Pressures of Mars‐Sized Bodies. Issue 11 (6th November 2021) - Piet, H.; Leinenweber, K.; Greenberg, E.; Prakapenka, V. B.; Shim, S.‐H.
Abstract: The large radius, and therefore low density, of the Martian core found in the InSight mission data analysis highlights the importance of considering other light elements besides sulfur (S), which has been considered as the main light element for Mars for decades. Hydrogen (H) is abundant in the solar system and becomes siderophile at high pressures. Although Fe‐S and Fe‐H systems have been studied individually, the Fe‐S‐H ternary system has only been investigated up to 16 GPa and 1723 K. We have investigated the Fe‐S‐H system at pressures and temperatures ( P ‐ T ) relevant to the cores of Mars‐sized planets (up to 45 GPa and well above the melting temperature of FeS) in the laser‐heated diamond anvil cell combined with in situ synchrotron X‐ray diffraction. We found that sufficient hydrogen leads to the disappearance of Fe3 S at high P ‐ T . Instead, separate Fe‐H and Fe‐S phases appear at 23–35 GPa. At pressures above 35 GPa, we found a new phase appearing while Fe‐S phases disappear and Fe‐H phases remain. Our analysis indicates that the new phase likely contains both S and H in the crystal structure (tentatively FeS x H y where x ≈ 1 and y ≈ 1). The observed pressure‐dependent changes in the phase relation may be important for understanding the structure and dynamics of the Martian core and the cores of Mars‐sized exoplanets. Plain Language Summary: The metallic cores of planets and satellites are believed to contain significant amounts of light elements such as hydrogen and sulfur. To understand how a planetary core forms and evolves through time, it is important to know how iron alloys behave at the pressure‐temperature conditions of the cores. The iron‐hydrogen and the iron‐sulfur alloy systems are well‐known even at the Earth's core conditions. However, the iron alloy systems with both sulfur and hydrogen together have been studied only for depths of smaller bodies like Ganymede. Using new experimental techniques, we study the behavior of the iron‐hydrogen‐sulfur alloy system at higher pressures and temperatures. We found that at intermediate depths, sulfur and hydrogen form two separate iron alloys, while at greater depths, a new iron alloy with both sulfur and hydrogen may form in the cores of Mars‐sized planets. This change in mineralogy with depth, therefore, suggests that the structure and dynamics in the cores of Mars‐sized planets could be much more complex if hydrogen can be added to the region as a light element. Key Points: Fe3 S is not present under sufficiently hydrogen‐rich conditions, being replaced by FeH x and FeS or FeS x H y and FeH x At 23–35 GPa, separate FeS and FeH x phases exist stably, whereas above 35 GPa, a new Fe alloy phase appears, which may contain both S and H Crystallization from an Fe‐S‐H liquid would lead to a complex core structure